Optimal selection of conductors in distribution systems using tabu search algorithm [Selección óptima de conductores en sistemas de distribución empleando el algoritmo búsqueda tabú] (2018)
An efficient methodology for the optimal selection of conductor in distribution systems through the implementation of the metaheuristic optimization technique called Tabu Search is presented in this paper. To represent the problem a mono-objective mathematical model of nonlinear mixed integer type is used. The minimization of investment costs of conductors and operating costs (power losses) for a study period of one year is considered as objective function. A single-phase equivalent system is used for the evaluation. The set of constraints relates to technical and operational characteristics of the system, which are assessed through a backward/forward sweep load flow. Initial configuration to tabu search algorithm is created by using a constructive heuristic that ensures feasibility of the initial solution; to generate the neighborhood strategies of tree searching and graph theory are used. In order to verify its applicability and efficiency, two test feeders of specialized literature are employed, obtaining better quality results than those reported in the literature. © 2018, Universidad de Tarapaca. All rights reserved.